Modern view of the classification, diagnostics and clinical manifestations of gingivitis in children and adolescents - Khomenko Л. О.; Ostapko О. І.; Golubeva І. М. (Actual Dentistry, 2022)
Summary. In the article the modern international classification of periodontal diseases is presented. The expediency of it use in the practice of pediatric therapeutic dentistry is justified. Emphasized that every child needs early diagnostic of periodontal tissue status and bleeding during probing can be used for this purposes. The clinical manifestations of different forms of gingivitis associated with biofilm are presented.